Saraz method adjustment for the quantification of ammonia emissions generated in opened or hybrid animal production facilities (2016)
The objective of this study was to evaluate the efficiency of the Saraz method in order to quantify ammonia emissions generated in opened or hybrid animal production facilities, and to determine an equation for the adjustment method. To do this, we developed beacon equipment, with input and output gas sectors, hoods and absorbent porous material. After the collection, the amount of ammonia captured in the environment was determined in the laboratory. Different ammonia concentrations were evaluated in addition to the different speeds of the exhaust air. Considering the results, it can be concluded that for the situations analyzed the Saraz method is efficient, but as with other methods, with an increase of air velocity and concentration, its efficiency decreases. An equation for the adjustment of the Saraz method was generated to determine the concentration and the rate of ammonia emissions inside animal facilities.